Higher wheat prices push Egypt to increase price of subsidized bread for first time since 1989 - Jovanovic, Nina; Glauber, Joseph W. (International Food Policy Research Institute, 2024)
In June 2024, the Egyptian government raised the price of subsidized traditional baladi bread to 20 piastres ($0.004)1 per loaf—quadrupling the old price of 5 piastres. The change—the first such increase since 1989—was triggered by a number of factors: Egypt’s heavy reliance on wheat imports due to limited arable crop base and growing population, along with high global wheat prices amid the Russia-Ukraine war, combined with the weakening of Egyptian pound (EGP) against the U.S. dollar in March 2024 and government efforts to reduce public spending.